PENCALONAN KEPALA DAERAH PADA PEMILIHAN SERENTAK 2020 DI SULAWESI SELATAN - Jurdi, Syarifuddin (Jurnal Politik Profetik, 2021)
The concurrent election 2020 in South Sulawesi faced dynamic circumstances as the pairs of candidates must fill the requirements when registering themselves. During the process of regional election, some cases happened in some regions in South Sulawesi. As an example, some candidates in some regions might lose support from the political parties in the middle of the election process as the support from the political party is unstable. On the other hand, special cases happened in two districts (Gowa and Soppeng), where there was only one single candidate for each region. Hence the struggle to get the support of a political party did not occur in both areas. In another region, Selayar, the individual candidate who has already fulfilled the minimum requirement still seeks support from political parties. All candidates tend to register themselves as fast as possible to prevent the failure in registration stage. Another case shows that there was a pair of candidates who failed to be a partner because they were tested positive for narcotics use, while two candidate pairs experienced a delay in registration because they were positive for Covid-19 and the had to wait until they were tested negative for Covid-19 before continuing to the medical check-up stage.